Management of endometrial cancer in patients aged 80 years and older: Identifying patients who may benefit from a curative treatment. (November 2019) - Benito, Virginia; Lubrano, Amina; Andújar, Miguel; Mori, Marta; Federico, Mario
Abstract: Objective: The goal of this study was to evaluate the demographic characteristics, pathology, treatment, prognostic factors and survival rates in elderly patients with endometrial cancer, and to compare their results with those of younger ones, in order to define the specific characteristics of this malignancy in this population. Study design: Retrospective analysis of all endometrial cancer patients managed at the University Hospital of the Canary Islands (Spain) between 1990 and 2016. Survival curves were calculated by using the Kaplan-Meier method and compared with the log-rank test. Logistic regression analysis was used to assess the independent effect of different variables on cancer-specific survival. Statistical significance was considered for p < 0.05. Results: The study included 1799 endometrial cancer patients; 170 of them (9.4%) were 80 years old or older. Elderly patients received less surgery (68.2% vs. 92.4%), lymphadenectomy (10.3% vs. 26.2%) and adjuvant treatment (37.1% vs. 51.2%) than younger ones, and presented higher probability of receiving palliative treatment (27.6% vs. 4%). Endometrioid tumors were more frequently diagnosed in younger patients (78.8% vs. 62.9%), while type 2-endometrial cancer was more frequently diagnosed in elderly ones (37.1% vs. 21.2%). Cancer-specific survival in older patients was significantly poorer than in younger ones, with a mean of 61.4 months (95%CI 51.7–71.1) versus 226 months (95%CI 218.9–233.1), respectively. In a multivariate analysis: age, FIGO stage, histology, tumor differentiation and adjuvant treatment were independently associated with survival. Conclusion: Although endometrial cancer is more aggressive in older patients, they are less likely to receive optimal treatment, which negatively affects their survival. Specific guidelines for the management of this population, including a comprehensive geriatric assessment, should be developed to improve their prognosis.